Congestion spill effects of Heathrow and Frankfurt airports on connection traffic in European and Gulf hub airports. (October 2016) - Redondi, Renato; Gudmundsson, Sveinn Vidar
Highlights: The aim of the paper is to estimate congestion spills of connections for Heathrow and Frankfurt. Congestion spills are estimated on 9 hub airports in Europe and the Middle-East using a panel approach. The results show asymmetric overall (European and intercontinental) connection spills for Heathrow and Frankfurt. Abstract: We develop two stage fixed-effects single-spill and double-spill models for congestion connection spills of London Heathrow and Frankfurt airports on 9 hub airports in Europe and the Gulf. Our panel data covers connection traffic from 1997 to 2013 for Heathrow and 1997 to 2011 for Frankfurt. The single-spill results support strongly that the connection spills from Heathrow's capacity limitations do strengthen competing hub airports of major alliance groups and to a lesser degree one Gulf hub. The double-spill model for Heathrow and Frankfurt shows nearly asymmetric overall spill characteristics between the two airports. Our results underline the influence of airline network strategies on congestion spills as European airline networks are shaped by alliances and umbrella mergers. Thus, the airline network perspective in airport capacity expansion decisions needs to play a greater role, as indicated by our asymmetric results for overall spill effects between Heathrow and Frankfurt airports.